Profitability And Profit Growth Of Manufacturing Companies In Indonesia During The Covid-19 Pandemic - Nuzulla, Firdausi; Murtianingsih, Murtianingsih (CV. Inara, 2022)
The purpose of this study is to determine and analyze the effect of Net Profit Margin (NPM), Return On Assets (ROA), and Return On Equity (ROE) on profit growth in manufacturing companies in Indonesia. This type of research is classified as causal associative, a study that aims to determine the relationship between two or more variables. All of the manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020 and selected as the research population were 194. A purposive sampling method adapted to the purpose was used in the selection of samples so that 16 companies were obtained as samples.This study uses quantitative data types, while the analytical techniques used are classical assumption test, multiple regression analysis, R2 coefficient of determination test and t test. Based on the results of the analysis, it is stated that profit growth in the manufacturing sector listed on the Indonesia Stock Exchange (IDX) in 2018-2020 is not significantly affected by the NPM, ROA and ROE variables..